Evaluation of the Quality of Diagnosis Coding for Pediatric Cases in Inpatient Medical Records - Widyaningrum, Linda (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2024)
Diagnosis codes are used for policy-making and determining healthcare costs, so they must be of high quality. Therefore, evaluation of diagnosis codes is necessary. The evaluation includes consistency (reliability), accuracy (validity), completeness, and timeliness. This study aimed to evaluate the quality of diagnosis coding for pediatric cases in inpatient medical records at Bagas Waras Regional General Hospital, Klaten, in 2023. This was a descriptive study with a retrospective approach. The sample used was 95 pediatric medical records, using a simple random sampling technique. The research instruments were ICD-10, observation guidelines, and interviews. Data processing involved collecting, editing, classifying, tabulating, and presenting data. Data analysis was descriptive. The quality of diagnosis codes can be seen from indicators such as code consistency (97.89%) and inconsistency (2.11%). Code accuracy (91.57%) and inaccuracy (8.43%). The code completeness was 96.84% and the code incompleteness was 3.16%. The code timeliness was 98.94% and the code inaccuracy was 1.06%. The diagnosis accuracy with examination and action was 100%. Factors that influence the quality of diagnosis codes are medical personnel (doctors), medical records personnel (coders), and other health workers. The author recommends establishing regulations regarding time limits for coding diagnoses and actions. Hospitals should hold training or seminars on coding more regularly to improve the skills and knowledge of coding staff and support code quality.